PEREMPUAN DAN ANAK DALAM TINDAK PIDANA TERORISME DI INDONESIA - Anjar Kartika Wening (2021)
Related to terrorism, in general, these crime were committed by men, but there is interesting fact in the case of suicide bombing that occurred in Surabaya in 2018, in which the suicide bombing was not only committed by men but also involves women and children. The involvement of women and children in terrorism, such as the suicide bombing in Surabaya, is a new mode used by terrorists to deceive the security apparatus, because this involvement was previously undetected so that the security apparatus could not predict it could be happen. The purpose of this research is to find out what are the factors that cause the involvement of women and children in terrorism and to find out how prevention efforts can be made. The research method used in this research is an normative juridical research method through a statutory approach and a conceptual approach. The results of this research explain that the factors that cause the involvement of women and children in terrorism in Indonesia are due to internal and external factors. Prevention efforts that can be done are by the State Defense efforts through Citizenship Education which are further carried out through the Development of State Defense Awareness such as Counter Radicalization, Counter Ideology, Counter Narrative, Education, Society and Society Leaders Role also Formation of Society Programs.